2016
DOI: 10.1007/s10811-016-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory culture experiments to study the effect of lignite humic acid fractions on iron solubility and iron uptake rates in phytoplankton

Abstract: Please Cite the article as: H. Hasegawa, Y. Tate, M. Ogino, T. Maki, Z.A. Begum, T. Ichijo and I.M.M. Rahman, Laboratory culture experiments to study the effect of lignite humic acid fractions on iron solubility and iron uptake rates in phytoplankton AbstractThe major fractions of dissolved iron in seawater exist as a complex with organic ligands. A high bioavailability of iron bound to humic acid (HA) compared to the other model ligands, such as desferrioxamine B or ferrichrome, has been reported, which impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…Humic colloids may well facilitate microbial respiration by providing hot spots for (bacteria to congregate as well as a localized source of nutrients. Recent work by Hasegawa et al (2017) provides some support for this hypothesis. They found that the highest intracellular iron uptake by Prymnesium parvum (haptophyte) occurred with the 10−30 kDa MW fraction of humics in seawater medium rather than with the LMW fraction.…”
Section: Humic Substances As a Versatile And Effective Source Of Bioamentioning
confidence: 90%
“…Humic colloids may well facilitate microbial respiration by providing hot spots for (bacteria to congregate as well as a localized source of nutrients. Recent work by Hasegawa et al (2017) provides some support for this hypothesis. They found that the highest intracellular iron uptake by Prymnesium parvum (haptophyte) occurred with the 10−30 kDa MW fraction of humics in seawater medium rather than with the LMW fraction.…”
Section: Humic Substances As a Versatile And Effective Source Of Bioamentioning
confidence: 90%
“…The comparative logK Fe for the ML species with different HA lignite size-fractions indicated the lowest value for larger MW fractions of HA lignite (>100 kDa). It could be correlated with the increased aggregation rate of corresponding HA lignite size-fraction in the aqueous matrix [35,56], either attributable to intermolecular H-bond formation via the protonation of HA lignite functional groups [57] or to the charge neutralization and cation bridge formation [58].…”
Section: Stability Constants Of the Ha Lignite Size-fractions With Ironmentioning
confidence: 98%
“…The HAs are assumed to be an assorted-assemblage of several smaller molecular fragments that are bound by weak dispersive forces, such as, van dar waals, π-π or CH-π interactions and so forth, to form supramolecular aggregates [33]. The disparity in conformational distribution among the HA lignite size-fractions via molecular characterization [34], or the corresponding impact of HA lignite -fractionation on iron solubility [35] has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying membrane permeability for various ionic species due to various HS effects, including complexation, generates elevated intracellular levels of redox-active ionic species, such as Fe 2+ , and ionic species acting as secondary messengers, e.g., Ca 2+ [ 67 , 68 ]. The ability of HS to complex ionic species, especially iron ionic species, is important for the HS effect on microalgae [ 69 ].…”
Section: Hormetic Effects Of Humic Substances On Microalgaementioning
confidence: 99%
“…The permeability change in the membrane of R. subcapitata depends on pH. The passive diffusion of fluorescent tracers through the membranes of R. subcapitata (synonym used Selenastrum capricornutum ) is higher at pH 5 than at pH 7 [ 67 ].…”
Section: Hormetic Effects Of Humic Substances On Microalgaementioning
confidence: 99%